Importance of Seminal Hyaluronidase Activity and Hypo-Osmotic Swelling Test in Male Infertility - A.S. Tambe; M.V. Sawane (Al Ameen Medical College, 2011)
The conventional seminal parameters like sperm density, motility, morphology, etc. are not perfect indicators of seminal functional quality. Hence, Seminal Hyaluronidase Activity (SHA) and Hypo-osmotic Swelling (HOS score) of sperms that evaluate healthy sperms of fertilizing potential, were studied in male partners of infertile couples. The semen samples were obtained, by masturbation after 4 days of abstinence, from recently Fertility Proven Males (Group-I, n=30) and Male Partners of Infertile Couples Normozoospermic (Group-II, n=30) and Oligozoospermic (Group-III, n=30)]. After performing routine seminal analysis, the semen samples were subjected for SHA and HOS score assessment. The mean  standard deviation values of SHA (mm of ring diameter) were 9.901.65, 8.771.87 and 6.501.33 in Group-I, Group-II and Group-III, respectively. Similarly, the mean  standard deviation values of HOS score (%) were 65.508.69, 58.7715.95 and 39.009.78 in Group-I, Group-II and Group-III, respectively. The difference in values of SHA and HOS score amongst different Groups was very highly significant statistically (p0.001). Also, we found significant correlation of SHA and HOS score with sperm density, % motility and % normal morphology. This study shows that Normozoospermic Infertile Males, although having normal conventional seminal parameters, have lower SHA and HOS score than Fertility Proven Males. Thus, it emphasizes the importance of SHA and HOS score assessment in infertile males.